Diseño organizacional y gestión del talento humano para la empresa proveedora de internet VILCANET de la parroquia Vilcabamba del cantón Loja. - Maza Madrid, Lady Guisella (2012)
No organizations or individuals no talent management, and it is used on the one hand, the ability of people to conquer and maintain their employees, and on the other hand the ability of firms to develop and use intellectual skills and competitive members. The company VILCANET is a private company domiciled in the parish of the canton Vilcabamba Loja, which aims to provide Internet service to the people of Vilcabamba, Loja and Zamora Chinchipe part. This paper entitled Organizational Design and Human Resource Management for the company providing Internet VILCANET the parish Vilcabamba Loja Canton, the main objective is to improve organizational design and talent management, with the aim of optimize the staff in the company VILCANET. The methodology is clearly set out the methods used, as well as research techniques: direct observation, interview directed the manager - owner of VILCANET and surveys of the 11 employees of the company, we have obtained shows the results for examination and interpretation. As for the results obtained. The company does not have an organizational structure identifying hierarchical levels, line of authority, and does not contain a manual setting functions responsibilities and functions. Emphasizing the Admissions Staff Stages applied to employees: first point is the recruitment being that 91% of employees known through personal references, selecting 24% presented resume and 35% not apply any selection technique, contraction only 36% of employees are hired and with respect to induction, training and motivating all these aspects are handled in the company in an empirical way. Job evaluation "VILCANET" this system applies not only handled in an empirical way. What if it was evident according to data obtained everything all company employees do not have a higher academic level are not yet prepared according to their daily roles in the company. Likewise, the Company's Performance Evaluation of an empirically applied on that ground 100% of employees agree that the evaluation. There is a diagnosis which knows its history and current situation of the company which mentions strengths that VILCANET has a favorable environment for work and a life of good leadership by the manager, and as a lack of weaknesses organizational structure and the lack of a manual functions. Then a proposal of a design of an organizational structure for "VILCANET", in order to record the achievement of organizational objectives raised. Finally it has been established conclusions and recommendations which are properly synthesized in an extract of the present investigation, finally presents the bibliography, appendices and index research.